Alexithymia and Suicide Risk in Psychiatric Disorders: A Mini-Review - De Berardis, Domenico; Fornaro, Michele; Orsolini, Laura; Valchera, Alessandro; Carano, Alessandro; Vellante, Federica; Perna, Giampaolo; Serafini, Gianluca; Gonda, Xenia; Pompili, Maurizio; Martinotti, Giovanni; Di Giannantonio, Massimo (Frontiers in Psychiatry, 2017)
IIt is well known that alexithymic individuals may show significantly higher levels of anxiety, depression, and psychological suffering than nonalexithymics. There is an increasing evidence that alexithymia may be considered a risk factor for suicide, even simply increasing the risk of development of depressive symptoms or per se. Therefore, the purpose of this narrative review was to elucidate the possible relationships between alexithymia and suicide risk. The majority of reviewed studies pointed out a relationship between alexithymia and increased suicide risk. In several studies this relationship was mediated by depressive symptoms. In conclusion, the importance of alexithymia screening in everyday clinical practice and the evaluation of clinical correlates of alexithymic traits should be integral parts of all disease management programs and, especially, of suicide prevention plans and interventions. However, studies limitations are discussed and must be considered.